Market Reaction To The Russian Vs Ukrainian War - Gilang Kharisma; Arum Pujiastuti; Feri Tristiawan (Institute of Computer Science (IOCS), 2022)
The purpose of this study is to investigate the impact of the Russian invasion of Ukraine on the Indonesian capital market. The sample employs Index 30 because it represents a group of companies with strong fundamentals and high liquidity. Using the event study research method, t = 0 is determined using the date of Russia's initial invasion of Ukraine, which occurred on February 24, 2022. In addition, this study uses secondary data from Yahoo Finance. Market model approach with an ordinary least square method is used to find abnormal returns in this research. Utilizing statistical testing using SPSS, the results revealed a significant negative reaction at t-3, or three days prior to Russia's invasion of Ukraine. In contrast, there was no significant difference between abnormal returns before and after the occurrence.